The Ipswich Touch Test (IPTT) has the Sensitivity and Specificity Equivalent to the Monofilament Test for the Detection of Diabetic Sensory Neuropathy - Revalina Silmy Alvira; Dahrizal Dahrizal; Idramsyah Idramsyah; Septiyanti Septiyanti; Widia Lestari (GLOBAL HEALTH SCIENCE GROUP, 2024)
The most common complication of diabetes is neuropathy. Diabetic foot screening includes secondary prevention efforts against further complications from diabetes. The need for practitioners to have practical, simple, and affordable sensory neuropathy screening techniques that can be independently is a demand in today's health services. A study aimed to assess the sensitivity and specificity of the ipswich touch test (IPTT) to the 10g monofilament test in the early detection of diabetic neuropathy. Methods: This quantitative observational research design used a cross-sectional method with 61 respondents who had diabetes mellitus for more than one year in the working area of the Pasar Ikan Health Center, Bengkulu City. Samples were taken by consecutive sampling. The researcher conducted an ipswich touch test (IPTT) first and then an examination with a monofilament test of 10g as the gold standard. The data is processed and analyzed with a computer application to see the sensitivity and specificity values. Ipswich touch test (IPTT) had a sensitivity value of 91.3%, specificity of 92.1%, positive predictive value of 87.5%, negative predictive value of 94.59%, positive probability ratio of 11.55, negative probability ratio of 0.09 and AUC value of 91%. The ipswich touch test (IPTT) has the same sensitivity, specificity, and accuracy as the monofilament test.